2001
DOI: 10.1021/bi015587o
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotides with Bistranded Abasic Sites Interfere with Substrate Binding and Catalysis by Human Apurinic/Apyrimidinic Endonuclease

Abstract: Apurinic/apyrimidinic endonuclease (AP endo) is a key enzyme in oxidative damage DNA repair. The enzyme, which repairs abasic sites, makes a single nick 5' to the phosphodeoxyribose, leaving a free 3'-hydroxyl. We recently described single turnover kinetics for human recombinant AP endo acting on an oligonucleotide with a single abasic site. We hypothesized that the structural changes induced by the presence of a second abasic site might provide insight into how AP endo recognizes the first abasic site. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…The stimulation of hNTH1 activity was independent of the enzyme activity of APE1. The assay mixture lacked MgCl 2 and contained sufficient EDTA to abrogate APE1-mediated endonucleolytic cleavage, but not the binding of APE1 to DNA (18). Identical experiments with Tg:G substrates showed no increase in hNTH1 substrate processing in the presence of APE1 (data not shown).…”
Section: Ape1 Increases Hnth1 Processing Of Tgmentioning
confidence: 94%
See 1 more Smart Citation
“…The stimulation of hNTH1 activity was independent of the enzyme activity of APE1. The assay mixture lacked MgCl 2 and contained sufficient EDTA to abrogate APE1-mediated endonucleolytic cleavage, but not the binding of APE1 to DNA (18). Identical experiments with Tg:G substrates showed no increase in hNTH1 substrate processing in the presence of APE1 (data not shown).…”
Section: Ape1 Increases Hnth1 Processing Of Tgmentioning
confidence: 94%
“…Enzyme, protein, and substrate were diluted to working conditions in assay buffer and equilibrated at 37°C. MgCl 2 -independent assays were performed with the above reaction buffer minus MgCl 2 in the presence of 5 mM EDTA, which permits binding of APE1 to DNA, but inhibits its endonuclease activity (18). Reactions contained 40 nM 32 P-5Ј-end-labeled 2Ј-deoxyribose oligonucleotide duplex substrate and 5 nM hNTH1 with or without 20 nM APE1.…”
Section: Methodsmentioning
confidence: 99%
“…1 In addition to the endogenously induced $10 000 abasic sites per cell per day, abasic sites are also created exogenously and as intermediates during repair of few other DNA damage lesions. 7,8 Clustered abasic sites are frequently induced by ionizing radiation, chemicals and various other factors. 4-6 A complicated situation is encountered when two or more abasic sites are present in close proximity giving rise to abasic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies suggest much slower rejoining kinetics for DSBs induced by high-LET radiations compared with low-LET radiations (25,26) reflecting the increased complexity of DSBs induced by high-LET radiation (27). Studies with synthetic oligonucleotides containing specific types of clusters suggest that clustered DNA lesions are resistant to processing by glycosylases or endonucleases (28)(29)(30)(31)(32)(33). In vivo studies have shown that the number of abasic clusters formed in human monocytes after irradiation did not return to background levels for over 14 days (14).…”
Section: Introductionmentioning
confidence: 99%